Stakeholder mapping to explore social and economic capital of Rotating Savings and Credit Associations (ROSCAs) to increase demand for and access to healthy food - Lukwa, Akim Tafadzwa; Wayas, Feyisayo A.; Lambert, Estelle Victoria, “Savings for Health” IDRC collaborators; Alaba, Olufunke; Foley, Louise; Harbron, Janetta; Lappeman, James; Levitt, Naomi; Mchiza, Zandile; Okop, Kufre; Oni, Tolu; et al. (Frontiers in Sustainable Food Systems, 2024)
South Africa, grappling with the complexities of malnutrition, faces a dual challenge of undernutrition in children and overnutrition in adults, particularly among women. This situation is exacerbated by high rates of food insecurity, affecting nearly one-fourth of households. In this context, the role of Rotating Savings and Credit Associations (ROSCAs), locally known as stokvels, becomes increasingly significant. These informal, often women-led, savings and borrowing groups present a unique opportunity to address dietary challenges and promote healthier eating practices in urban, low-income settings.This study explores the potential of stokvels in mitigating the dual burden of malnutrition by facilitating access to healthy, affordable foods. We conducted stakeholder mapping to understand the roles and influences of various actors within South Africa's food system, particularly their interactions with stokvels. Our research focuses on how these groups, deeply embedded in the community fabric, can leverage their collective power to negotiate better access to nutritious food and influence healthier